2008
DOI: 10.1002/pssc.200776531
|View full text |Cite
|
Sign up to set email alerts
|

Exact method to solve the Boltzmann equation to any order in the driving forces: Application to transport parameters

Abstract: In this paper a method to compute transport parameters in semiconductor devices as a function of the driving forces is presented. The method is based on an exact expansion of the distribution function (solution of the Boltzmann transport equation) in a series in the electric field and the gradient of the quasi‐Fermi potential. Eventhough this series probably diverges for high fields, it is still usable for low and moderate field intensities. Results for silicon clearly show that the usual parametrization of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…(2) shows that the preponderate DF are the gradient of the quasi-Fermi potential, the electric field, and surprisingly the second derivative of the quasi-Fermi potential. In Section III it is shown that in small N IN structures the second derivative of the quasi-Fermi potential dominates, with the unfortunate consequence, that in such structures no natural TCAD mobility (in the sense of [1]) can be defined anymore.…”
Section: Totmentioning
confidence: 99%
See 3 more Smart Citations
“…(2) shows that the preponderate DF are the gradient of the quasi-Fermi potential, the electric field, and surprisingly the second derivative of the quasi-Fermi potential. In Section III it is shown that in small N IN structures the second derivative of the quasi-Fermi potential dominates, with the unfortunate consequence, that in such structures no natural TCAD mobility (in the sense of [1]) can be defined anymore.…”
Section: Totmentioning
confidence: 99%
“…2is valid, a conservative criterion has been used: TP are not allow to change by more than 25% of their equilibrium value. Using the notation of [1], this criterion can be mathematically written as…”
Section: B Couplingmentioning
confidence: 99%
See 2 more Smart Citations
“…In a state of equilibrium a gas of particles has uniform composition with constant temperature and density. If the gas is subjected to a temperature difference or disturbed by externally applied electric, magnetic, or mechanical forces, it will be set in motion and the temperature, density, and composition may become functions of position and time, in other words, the gas moves out of equilibrium [6][7][8][9]. The Boltzmann Equation applies to a quantity known as the distribution function, which describes this non-equilibrium state mathematically and specifies how quickly and in what manner the state of the gas changes when the disturbing forces are varied.…”
Section: Introductionmentioning
confidence: 99%